Pengaruh Kepemimpinan Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Karunia Tirtamas Abadi - Abd. Azis, Rusdiaman Rauf, Ronny Ahmad Al Asirie (STIE AMKOP, 2023)
The objectives of this study are (i). to analyze the direct influence of leadership on employee performance; (ii) to analyze the effect of job satisfaction on employee performance; (iii). To determine the simultaneous effect of leadership and job satisfaction on employee performance This study used a survey method with a sampling technique, namely a saturated sample, namely permanent employees totaling 30 respondents. Data were analyzed using linear regression, multiple regression and determination tests. The results showed that: (i). Leadership directly has a positive and significant effect on employee performance, (ii). Directly job satisfaction has a positive and significant effect on employee performance, and (iii) Directly and simultaneously leadership and job satisfaction have a positive and significant effect on employee performance. Keywords: Leadership, Job Satisfaction, Employee Performance